Modelado y simulación de la dispersión de contaminantes en la pluma de una chimenea por el método de dispersión Gaussiano - Pérdiz Dávila, José Manuel (2017)
The present work used the Gaussian dispersion methodology to determine the possible concentration of pollutants in a chimney pen, for which we used the programming languages called Visual Basic, MatLab and Excel, obtaining a result that when compared with a similar application (EPA SCREEN3) has a deviation of 3% relative to ECREEN3, being considered adequate to be used.